Analisis Pengaruh Ukuran Perusahaan, Profitabilitas, Kompetisi, Pertumbuhan Penjualan, Rasio Utang, dan Kualias Auditor Terhadap Pengungkapan Emisi Karbon Perusahaan Sektor Aneka Industri BEI Tahun 2019-2022 - Kamila, A Shafa Sahra (Cattleya Darmaya Fortuna, 2024)
The public's attention has been drawn to the problem of global warming because of the rise in carbon emissions brought on by businesses' increased productivity. By requiring businesses to record their carbon emissions in their yearly reports and to reduce them, the Indonesian government is attempting to prevent negative repercussions. Financial and non-financial variables may contribute to the disclosure of carbon emissions. This study demonstrates that firm size and sales growth are two characteristics that encourage businesses to disclose carbon emissions more openly. Conversely, the organization reduces the goal of carbon emission disclosure in audit quality. Meanwhile, company carbon emission disclosure is not significantly impacted by debt ratio, competition, or profitability.